PHYTOCHEMICALSCREENING AND ANALYSIS POLYPHENOLIC ANTIOXIDANT ACTIVITY OF METHANOLIC EXTRACTOF WHITE DRAGON FRUIT (Hylocereus undatus) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
White dragon fruit is a well known and widely used herbal medicine, especially in Asia, which contains several interesting bioactive constituents and possesses health promoting properties. The aim of this study was to analyze for the bioactive compounds, evaluate total phenolic contents and antioxidant capacities of methanolic extract of white dragon fruit. The antioxidant activity was determined by the 1,1-diphenyl-2- picrylhydrazyl (DPPH) free radical scavenging activity assay. Total phenolic content were determined by Folin-Ciocalteu method. Phytochemical screening of the white dragon fruit showed the presence of triterpenoid, alkaloid, flavonoid and saponin. The extract exhibited strong antioxidant activity with IC&#8325